Sistem Pakar Mendeteksi Penyakit Kulit Pada Sapi Menggunakan Metode Forward Chaining di Dinas Peternakan Kabupaten Rokan Hulu - Hendri Maradona (RJOCS (Riau Journal of Computer Science), 2015)
Knowledge of skin disease in cattle in the community in an effort to identify early disease to make their own decisions is still low. Dependence on knowledge Veterinarian for detecting cow skin disease remains a top priority, especially for cattle farmers in Rokan Hulu in an effort to determine a skin disease that threatens their cow. So the cost to society is quite expensive and also seen from time highly inefficient. Therefore, the use of media consulting expert system-based computer that uses factsand reasoning techniques in solving the problems of the dairy farmers in Rokan Hulu can be solved by the method of Forward Chaining. Application Expert System produces output in the form of an application program or tool that can be used to diagnose the possibility of skin disease in cattle based on symptoms entered by the user and the application is using a technique or method trace forward (forward chaining) to make sense of cow skin diseases. Testing of the system shows that the system isable to perform diagnostics cow skin diseases based on symptoms suffered. This application was built using Microsoft programming language Visual Basic 6.0 and its data processing applications with Microsoft Access 2003